Marketing Strategy UMKM Dengan CRISP-DM Clustering & Promotion Mix Menggunakan Metode K-Medoids - Iswavigra, Dwi Utari; Endriani Zen, Lova; Okfalisa; Hanim, Hafizah (Jurnal Informasi dan Teknologi, 2023)
The development of MSMEs is something that has a very large influence on the economy in Indonesia. The local MSME market is even able to compete globally as shown by the large number of incoming requests from abroad. Even so, MSMEs in Indonesia have experienced fluctuations due to the economic crisis. The fluctuations that occurred showed a decrease in the number of MSMEs by 0.003%. The Executive Director of the Institute For Economics (Indef) said that the fluctuations that occurred in MSMEs resulted in unstable economic development in the second quarter. From this problem, the CRISP-DM Clustering process was carried out to process existing MSME data to determine the right promotion strategy in developing MSMEs based on the type of business undertaken, turnover and assets owned. This research was conducted using the K-Medoids algorithm by forming 3 clusters for data processing. The data processed were 71 MSME data throughout Solo Raya, where in cluster 1 there were 25 MSMEs which were dominated by types of businesses in the fashion sector with an average turnover and assets between IDR 1,000,000 - IDR 5,000,000. Cluster 2 consists of 39 MSMEs which are dominated by types of businesses in the culinary field with average turnover and assets between IDR 1,000,000 - IDR 5,000,000 and in cluster 3 as many as 7 MSMEs which are dominated by types of businesses in other fields ( excluding 6 other types of business) with an average asset of ≥ Rp. 30,000,000 and a turnover between Rp. 21,000,000 - Rp. 25,000,000.